DOI: 10.11606/d.22.2013.tde-26092013-162402
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade de vida relacionada à saúde e expectativas de pacientes antes do tratamento cirúrgico da estenose lombar

Abstract: À minha família querida. Aos meus pais, José e Nilza, por todo cuidado, respeito e amor incondicional a mim dedicado sempre.Aos meus irmãos, Simone, Daniela e José Henrique, e a meus sobrinhos amados, Mateus e Luísa sempre presentes e torcendo por mim. AGRADECIMENTOSA Deus, pelo dom da vida, e por tantas bênçãos de amor e proteção. À Profa. Dra. Rosana Aparecida Spadoti Dantas, minha orientadora, pela sabedoria compartilhada, por tanto carinho, dedicação, paciência e respeito, por saber aceitar meus medos, ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Moreover, some studies evaluated depression symptoms, in the sense of existing a possible association with poor quality of life. [11][12][13]38 In a systematic review, the authors concluded that depression may predict unfavorable results regarding functional capacity and the severity of symptoms caused by degenerative disorders of the spine, such as spinal stenosis. 37 Regarding functional limitation, participants with lumbar stenosis had about 10% more functional limitation than those with cervical stenosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, some studies evaluated depression symptoms, in the sense of existing a possible association with poor quality of life. [11][12][13]38 In a systematic review, the authors concluded that depression may predict unfavorable results regarding functional capacity and the severity of symptoms caused by degenerative disorders of the spine, such as spinal stenosis. 37 Regarding functional limitation, participants with lumbar stenosis had about 10% more functional limitation than those with cervical stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, surgical treatment does not ensure the improvement of all symptoms caused by stenosis, which might cause a worsening in the physical and emotional clinical condition of patients. [5][6][7][10][11][12][13] In addition to the functional analysis of the surgical results, in the last few years, researchers have been searching for a subjective analysis regarding the health condition of these people. Therefore, perspectives of patients on the evaluation of signs and symptoms of the disorder, health-related quality of life (HRQOL), 11,[14][15][16] pain, functional aspects, 6,17-19 expectations [20][21][22][23] and satisfaction with the treatment [24][25] have been sought.…”
Section: Introductionmentioning
confidence: 99%